HUBUNGAN ANTARA MOTIVASI BELAJAR DAN PERSEPSI SISWA TERHADAP KINERJA GURU DALAM MENGELOLA KEGIATAN BELAJAR DENGAN HASIL BELAJAR IPA SISWA KELAS VIII DI SMPN N 1 PACITAN - PALUPI, RETNO (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
In terms of learning, motivation is defined as the overall driving force in students to perform a series of learning activities in order to achieve those objectives. Teachers task is motivating the child so that he will do a series of learning activities. High motivation of the students is expected to drive the students interest in learning so that student learning outcomes can be improved.Human resources in this research are8th grade Student at SMP N 1 Pacitan. The objective of this research was to determine: (1) The relationship between learning motivation toward Science Learning Outcomes of 8th grade Student at SMP N 1 Pacitan.. (2) The relationship between student perceptions of teacher performance in managing learning activities toward science learning outcomes of 8th grade Student at SMP N 1 Pacitan. (3) The relationship between learning motivation and student perceptions of teacher performance in managing learning activities toward science learning outcomes of 8th grade Student at SMP N 1 Pacitan.This is quantitative research. Data collection technique used a Likert scale questionnaire. Analysis using correlation analysis techniques and multiple regression analysis with prerequisite test, analysis product moment correlation and multiple regression.The magnitude of the correlation between variables of X1 and Y is equal to 0.503> 0.159. The magnitude of the correlation between variables X2 to Y is equal to 0.394 >0.159.Based on the result of this research can be concluded that there is relationship between studentsâ learning motivation and teachers performance in learning activities by together towards science learning outcome of student at SMP Negeri 1 Pacitan.Â Keywords: Motivation, Teacher Performance in Managing Learning Activity, Learning Outcomes